Helium broadening parameters of water vapor in the 10,200-11,200 cm-1 spectral region; Journal of Molecular Spectroscopy; Vol. 331 - Petrova T. M. Tatiana Mikhaylovna; Solodov A. M. Aleksandr Mikhaylovich; Solodov A. A. Aleksandr Aleksandrovich; Deychuli V. M. Vladimir Mikhaylovich; Starikov V. I. Vitaly Ivanovich (2017, 2017)
Title screen